The importance of rational use of antibiotics in reducing environmental and public health impacts: A critical review (Research, Society and Development, 2025)
The consumption of antibiotics in human and animal health has increased significantly over the years, leading to irrational use and the spread of antibiotic resistance in bacteria. This study aims to investigate the impact of antibiotic resistance on the environment and public health through a narrative review of articles and reports published between 2014 and 2024. Searches were conducted using different databases and the search terms were "drug contamination," "water contamination," "medical waste," "drug resistance," "antibiotics," "rational use of medicines," and "environment," and different databases were used. The results show that animal excretions and inappropriate disposal of antibiotics have facilitated the spread of resistance genes through contamination of rivers and water sources, and consumption of contaminated meat and food. This has affected public health through the ineffectiveness of antibiotics and increased mortality from infections with antibiotic-resistant bacteria. Rational use of antibiotics combined with health education is essential to prevent irrational use and inappropriate disposal of antibiotics. These approaches can help reduce the impact on public health and the environment.